Two New Sulfate-Modified Dibenzopyrones With Anti-foodborne Bacteria Activity From Sponge-Derived Fungus Alternaria sp. SCSIOS02F49 - Chen, Yaping; Liu, Chuanna; Kumaravel, Kaliaperumal; Nan, Lihong; Tian, Yongqi (Frontiers in Microbiology, 2022)
To find novel antibacterial compounds, three sponge-derived fungal strains (SCSIOS02F40, F46, and F49) were investigated. As a result, Alternaria sp. SCSIOS02F49 was selected for investigation on its secondary metabolites, because its ethyl acetate (EtOAc) extract of PDB culture showed rich metabolites and strong antibacterial activity. Then, two new dibenzopyrones with rare sulfate group (1-2), together with ten known compounds (3-12) were isolated. Their structures were confirmed by NMR, MS data, and comparison with data of the relevant literatures. Almost all compounds showed moderate inhibitory activity against eight foodborne bacteria with MIC values in the range 15.6-250 μg/mL, and MBC values in the range 31.3-250 μg/mL. The antibacterial mechanism of 1 was preliminarily investigated using growth curves, scanning electron microscopy, and flow cytometry, which revealed that 1 altered the external structure of S. aureus and caused the rupture or deformation of the cell membranes. This research provides lead compounds for the development of new antibiotics or microbial preservatives.